IMPLEMENTASI SYARAT MATERIIL RESTORATIF JUSTICE UNTUK PELAKU PENGULANGAN TINDAK PIDANA BERDASARKAN PUTUSAN PENGADILAN DI WILAYAH HUKUM POLRES SIAK - Manurung, Fernando; Kadaryanto, Bagio; Winstar, Yelia Nathassa (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
In Article 5 letter e of the Republic of Indonesia State Police Regulation Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice states that the Material Requirements as intended in Article 4 letter a, are not perpetrators of repeat criminal acts based on Court Decisions. The purpose of this research is to analyze the implementation of material restorative justice requirements for repeat criminals based on court decisions in the legal area of ​​the Siak Police, to analyze obstacles and efforts to overcome obstacles in the implementation of material restorative justice requirements for repeat criminals based on court decisions in the legal area. Siak Police. The method used is sociological legal research. Based on the research results, it is known that the implementation of material requirements for restorative justice for perpetrators of repeat crimes based on court decisions in the jurisdiction of the Siak Police is not running optimally because especially at the Siak Police, restorative justice is not carried out repeatedly because in general the same criminal acts are given sanctions. in accordance with applicable regulations. Obstacles in implementing material restorative justice requirements for repeat criminals based on court decisions in the jurisdiction of the Siak Police are social stigma against recidivist perpetrators, lack of understanding in implementing these police regulations in the jurisdiction of the Siak Police, and law enforcers at the Siak Police show resistance to implementation. restorative justice, and taking a more repressive approach. Efforts to overcome obstacles in implementing material requirements for restorative justice for repeat offenders based on court decisions in the Siak Police jurisdiction include encouraging policies that support improving social stigma towards recidivist offenders, improving education and training, and law enforcers can strive for second Restorative Justice. Repeat offender of the same crime.